Genetic access to neurons in the accessory optic system reveals a role for Sema6A in midbrain circuitry mediating motion perception. Issue 1 (11th November 2018) - Lilley, Brendan N.; Sabbah, Shai; Hunyara, John L.; Gribble, Katherine D.; Al‐Khindi, Timour; Xiong, Jiali; Wu, Zhuhao; Berson, David M.; Kolodkin, Alex L.
Abstract: The accessory optic system (AOS) detects retinal image slip and reports it to the oculomotor system for reflexive image stabilization. Here, we characterize two Cre lines that permit genetic access to AOS circuits responding to vertical motion. The first ( Pcdh9‐Cre ) labels only one of the four subtypes of ON direction‐selective retinal ganglion cells (ON‐DS RGCs), those preferring ventral retinal motion. Their axons diverge from the optic tract just behind the chiasm and selectively innervate the medial terminal nucleus (MTN) of the AOS. Unlike most RGC subtypes examined, they survive after optic nerve crush. The second Cre‐driver line ( Pdzk1ip1‐Cre ) labels postsynaptic neurons in the MTN. These project predominantly to the other major terminal nucleus of the AOS, the nucleus of the optic tract (NOT). We find that the transmembrane protein semaphorin 6A (Sema6A) is required for the formation of axonal projections from the MTN to the NOT, just as it is for the retinal innervation of the MTN. These new tools permit manipulation of specific circuits in the AOS and show that Sema6A is required for establishing AOS connections in multiple locations. Abstract : The authors characterize mouse lines labeling retinal ganglion cells and brain neurons in the Accessory Optic System. Pcdh9‐Cre + RGCs prefer ventral motion, target the medial terminal nucleus (MTN) and survive after optic nerve crush. Postsynaptic MTN targets of these RGCs require Sema6A to form connections with other AOS nuclei.